Uterine artery Doppler velocimetry at mid‐term gestation as a potential predictive factor for the resolution of placenta previa at the end of third trimester of pregnancy - Lu, Yu; Wu, Yilun; Yang, Lijuan; Huang, Fan; Ren, Min (The journal of obstetrics and gynaecology research, 2020)
Aim The incidence of placenta previa before the third trimester is high. But many cases resolve as pregnancy progresses. Our study was to evaluate the efficacy of uterine artery Doppler velocimetry at mid‐term gestation for predicting placenta previa resolution in third trimester. Methods A single‐center retrospective study was done. A study cohort of 504 subjects with placenta‐cervix os distance measured both at 22–24 weeks and after 36 weeks of gestation and uterine artery Doppler velocimetry measured at 22–24 weeks of gestation were selected. The subjects were assigned to control group (n = 351), resolving group (n = 89) and placenta previa group (n = 64) according to their diagnosis of placenta previa at mid‐term and the end of the third trimester. The averages of the bilateral ratio of uterine artery systolic to end‐diastolic maximum blood flow velocity (S/D ratio), pulsatility index (PI) and resistance index (RI) were used for analysis. Results The means of S/D ratio, PI and RI of uterine arteries in the placenta previa group were significantly lower than that in either control group or resolving group. No differences were observed between control group and resolving group. The areas under the receiver operating characteristic curve were 0.7632, 0.7579 and 0.7644 for the means of S/D ratio, PI and RI, respectively (P < 0.0001). Conclusion The means of S/D ratio, PI and RI of the uterine arteries at mid‐term gestation are reduced in patients with persistent placenta previa, indicating unique pathogenic changes at mid‐term gestation, and have the potential to be a predictive factor on placenta previa resolution.